Penentuan sudut arah angin ion pada lucutan korona positif berkonfigurasi elektroda titik-bidang - Sumariyah Sumariyah; Maryam Restiwijaya; Muhammad Nur (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Determination of the ion wind angle of positive corona discharge with point to plane electrode geometry configuration has been done. Point electrode was made from stainless steel with various radiuses of 0.26 mm, 0.28 mm, 0.35 mm, and 0.47 mm. The plane electrode with circle form was made from stainless steel with diameter of 20 cm. Determination of the ion wind angle was carried out by measuring the current, the radius of deformation of lubricating oil at various voltage, electrode spacing, and the radius of the point electrode. The results showed that the angle of the ion wind direction is affected by a given voltage, the distance between electrodes, and the radius of the point electrode. Value of the ion wind flow direction angle is inversely proportional to the distance between the electrode and the radius of the point electrode. When the voltage is increased, the angle of ion wind direction will be larger but would reach saturation at the region of corona discharge which is close to the arc discharge.Keywords: Ion wind, positive corona discharges, point to plane electrode.